Efektivitas Model Cooperative Learning Tipe Jigsaw Pada Mata Pelajaran Dasar-dasar Ketenagalistrikan Di SMK Negeri 2 Sungai Penuh - M Najmi Saputra; Elfizon Elfizon (Journal of Electrical Vocational Education, 2025)
This study aims to examine the impact of implementing the Cooperative Learning model of the Jigsaw type on the learning outcomes of Grade X TITL 1 students in the subject Productive Basics of Electrical Power at SMK Negeri 2 Sungai Penuh. To improve student learning outcomes, a learning model that aligns with the learning objectives and characteristics is required, as the learning model greatly influences student achievement. The research method used is a pre-experimental design with a one-group pre-test and posttest model. The subjects of this study were Grade X TITL 1 students of SMK Negeri 2 Sungai Penuh for the 2024/2025 academic year. This study compares the initial scores obtained from the pre-test with the final scores obtained after the implementation of the Cooperative Learning Jigsaw model. The instruments used in this study were pretest and post-test questions. The results show an improvement in student learning outcomes, indicated by an increase in the average student score from 53.68 to 85.84. This is supported by an Effect Size of 2.58, which falls into the "Large" category. Therefore, the implementation of the Cooperative Learning Jigsaw model in the Productive Basics of Electrical Power subject for Grade X TITL 1 at SMK Negeri 2 Sungai Penuh can improve student learning outcomes. This is evident from the students’ scores, which increased from below the Learning Objective Achievement Criteria (pre-test) to meeting the criteria (post-test).